A life-saving therapy in Class I HELLP syndrome: Therapeutic plasma exchange. Issue 2 (April 2015) - Erkurt, Mehmet Ali; Berber, Ilhami; Berktas, Hacı Bayram; Kuku, Irfan; Kaya, Emin; Koroglu, Mustafa; Nizam, Ilknur; Bakırhan, Fatma Acar; Ozgul, Mustafa
Abstract: HELLP syndrome, which can affect multiple organ systems and cause maternal and fetal mortality, is a serious complication of pregnancy characterized by microangiopathic hemolytic anemia, elevation of liver enzymes, and thrombocytopenia. Delivering the infant usually suffices for the treatment of this syndrome. In cases with Class I HELLP syndrome, however, the clinical picture may rapidly deteriorate despite delivery. In this paper we presented the outcomes with the use of therapeutic plasma exchange in cases with class I HELLP syndrome. This study included 21 patients diagnosed with the Class I HELLP syndrome at Inonu University Faculty of Medicine, Department of Hematology between 2011 and 2014. A central venous catheter was placed and plasma exchange therapy was begun in patients unresponsive to delivery, steroid, and supportive therapy (blood and blood products, antihypertensive therapy, intravenous fluid administration, and antibiotics) within 24 hours after the diagnosis of Class I HELLP syndrome according to the Mississippi Criteria. All patients underwent therapeutic plasma exchange for three sessions each with a 1:1 volume. Hemogram and biochemical parameters of the patients were evaluated before and after the procedure. According to results, there was a statistically significant decrease in total bilirubin, LDH, AST, and ALT levels whereas a significant increase in platelet count was observed. Hemoglobin levels were increased, although this increase was not statistically significant. HELLP syndrome is primarily treated with the delivery of infant; however, some cases may show disease progression despite completion of delivery. As a potential cause of both maternal and fetal mortality, HELLP syndrome condition should be aggressively treated. Therapeutic plasma exchange is one of the available treatment options. Our study has found that postpartum use of plasma exchange therapy within 24 hours is an efficient and lifesaving treatment choice in Class I HELLP syndrome.